2018
DOI: 10.1371/journal.pone.0207370
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on crop yield, soil water balance and nitrate leaching in the semiarid and humid regions of Canada

Abstract: The impact of climate change on agricultural systems is a major concern as it can have a significant effect on the world food supply. The objective of this study was to evaluate climate change impacts on crop production and nitrate leaching in two distinct climatic zones in Canada. Spring wheat (Triticum aestivum L.) was selected for the semiarid regions of Western Canada (Swift Current, SK) and maize (Zea mays L.) was chosen for the more humid regions of central Canada (Woodslee, ON). Climate scenarios were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 68 publications
5
52
0
3
Order By: Relevance
“…Crop yields are sensitive to climate variations (e.g., [1][2][3]. It is undisputed truth that the climate change shows impact on the crop yields [4]. An increase of 1 to 2 • C temperature during the crop growing period causes crop dehydration and greatly reduces the grain production in regions such as the North China Plain, Indo-Gangetic Plains and the corn belt of the United States [5].…”
Section: Introductionmentioning
confidence: 99%
“…Crop yields are sensitive to climate variations (e.g., [1][2][3]. It is undisputed truth that the climate change shows impact on the crop yields [4]. An increase of 1 to 2 • C temperature during the crop growing period causes crop dehydration and greatly reduces the grain production in regions such as the North China Plain, Indo-Gangetic Plains and the corn belt of the United States [5].…”
Section: Introductionmentioning
confidence: 99%
“…Given the stated, the main aim of this study is to analyze recent climate change in the Semberija region and to investigate the effects of the determined climate change patterns on agricultural production, primarily on the production of corn, the most important crop over this area, and for which studies (Deryng et al, 2016;He et al, 2018;Knox et al, 2016;Olesen et al, 2011;etc. ) found that it will be much more vulnerable to climate change in relation to other crops.…”
Section: Mateријали и методеmentioning
confidence: 99%
“…Потенцијални утицаји климатских промјена на приносе пољопривредних култура постају све важније питање, које изазива велику забринутост у свијету посљедњих деценија због уочених негативних утицаја на производњу усјева и сигурност снабдијевања човјечанства храном (He et al, 2018;Zhang, Zhao, Chen, Guo, & Wang, 2015). Бројне студије истраживале су ефекте климатских промјена на производњу усјева (Cai, Wang, & Laurent, 2009;Ceglar & Kajfež-Bogataj, 2012;Deryng, Conway, Ramankutty, Price, & Warren, 2016;He et al, 2018;Kang, Khan, & Ma, 2009;Knox, Daccache, Hess, & Haro, 2016;Lobell & Gourdji, 2012;Matiu, Ankerst, & Menzel, 2017;Olesen et al, 2011;Rosenzweig et al, 2014;Ummenhofer et al, 2015;Zhang et al, 2015). Ипак, у Босни и Херцеговини ово питање још је недовољно истражено.…”
unclassified
See 2 more Smart Citations